The Implementation of Differential Analysis in Ultra-Micro Manufacturing Business - Frida Fanani Rohma; Andin Vivian Febrianti (Best Journal of Administration and Management, 2022)
This research aims to investigate the implementation of differential analysis in ultra-micro manufacturing businesses. The literature shows the role of differential analysis in cost allocation decisions. Consideration of costs and benefits to be gained becomes the main focus when conducting differential analysis. This research was conducted with a qualitative method. This research shows that management has not applied differential analysis in calculating the cost of goods manufactured for special orders. The differential analysis plays an important role especially in the decision-making to accept or reject special orders. This research shows that the proposed alternatives can accept special orders as long as the production capacity is adequate. The research findings indicate that based on the results of the differential analysis, management should choose an alternative to buying raw materials because it is more profitable than producing them yourself. Managers should start applying differential cost analysis so that special orders can be used as an alternative to increasing company profits.